A Study of Students’ Speech Acts in Organizational Education and Regeneration Program - Harmita Sari; Puspa Sari (Universitas Cokroaminoto Palopo, 2020)
This article aimed to describe, analyze, and explain the forms of speech acts of students after joining organizational education and regeneration program at Universitas Muhammadiyah Palopo. This research is a descriptive qualitative study that attempted to explain the speech acts that occur in the conversation. The subjects of this study were active students who had participated in the program. Data were taken from the results of observations, interviews, recording, and additional information in the field. The results of the research showed that the forms of the student speech act in the campus environment were (a) declarative, (b) imperative, and (c) interrogative.